Climate-adaptive Design and Performance Optimization of Double-layer Hollow Topology Interlocking Roof Tiles - Jiang, Wenqing; Peng, Xiangmin; Jin, Mingyu; Song, Bo; Hao, Dawei (Journal of Research in Science and Engineering, 2025)
Aiming at the problems of insufficient thermal insulation performance, poor structural stability and complex installation process of traditional roof structures, a new type of double-layer hollow topological interlocking roof tile system is proposed in this study. By introducing its structure, the composite thermal insulation principle driven by thermal pressure-wind pressure coupling is revealed. Focusing on the thermal insulation performance of the double-layer hollow topological interlocking roof tile, the technical route of combining computational fluid dynamics (CFD) simulation with dynamic thermal performance simulation verification is adopted. The parametric three-dimensional model is established by Rhino, and the architectural morphology is combined with computational fluid dynamics. The Phoenics software is used to simulate the fluid dynamics of the hollow layer height (0-140 mm), and the optimal hollow layer height is determined to be 80 mm. Further combined with Ladybug + Honeybee to carry out thermal performance simulation verification, under typical summer solstice conditions, the indoor air temperature of the roof system is 21 % lower than that of the ordinary roof, which verifies the hot pressing-wind pressure composite driving mechanism. The research results provide a quantitative design basis for high-performance roof systems.